Anti-ulcer activity of Bombax buonopozense P. Beauv. aqueous leaf extract (Fam: Bombacaceae) - Nwagba, C. A; Ezugwu, C.O; Eze, C.C; Anowi, F.C; Ezea, S.C; Nwakile, C. D. (Journal of Applied Pharmaceutical Science, 2013)
The objective of this study was to investigate the anti-ulcer activity of leaves of Bombax buonopozense P. Beauv. (Bombacaceae) in rats. Fresh dried leaves of B.buonopozense were extracted by cold maceration which yielded a mucilaginuous aqueous extract. Anti-ulcer effects of the aqueous extract at 100, 200 and 400 mg/kg were evaluated in rats using ethanol-induced ulcer model. Phytochemical analysis and lethality tests (LD50) were carried out using standard procedures. Results showed that the aqueous extract exhibited significant (P
Keywords: Anti-ulcer activity, B. buonopozense